2011
DOI: 10.1002/joc.2275
|View full text |Cite
|
Sign up to set email alerts
|

Total ozone and surface UV trends in the United Kingdom: 1979–2008

Abstract: ABSTRACT:In this study we present the UK's total ozone and UV data records, their measurement and preliminary processing, and discuss the observed trends. Notably, we combine the records from the Camborne and Reading sites to obtain a single ozone data series for southern England -a total duration of 30 years.Two-section linear trends and cross-over years are determined for Lerwick and southern England, both annually and seasonally. The observed minimum using this technique in the UK ozone record is found to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 26 publications
2
53
0
Order By: Relevance
“…The successful implementation of the Montreal protocol decelerated the weakening of the ozone layer (Egorova et al, 2013;Mäder et al, 2010;Newman and McKenzie, 2011) and many recent studies indicate the first signs of recovery over the Northern Hemisphere (Kuttippurath et al, 2013;McLinden and Fioletov, 2011;Newchurch et al, 2003;Smedley et al, 2012). Signs from the onset of ozone recovery since the late 1990s on surface UV-B irradiance have been mainly detected over the northern high latitudes; recent studies indicate that UV-B has been declining during the last 2 decades (Bernhard, 2011;Eleftheratos et al, 2014).…”
Section: Fountoulakis Et Al: Short-and Long-term Variability Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…The successful implementation of the Montreal protocol decelerated the weakening of the ozone layer (Egorova et al, 2013;Mäder et al, 2010;Newman and McKenzie, 2011) and many recent studies indicate the first signs of recovery over the Northern Hemisphere (Kuttippurath et al, 2013;McLinden and Fioletov, 2011;Newchurch et al, 2003;Smedley et al, 2012). Signs from the onset of ozone recovery since the late 1990s on surface UV-B irradiance have been mainly detected over the northern high latitudes; recent studies indicate that UV-B has been declining during the last 2 decades (Bernhard, 2011;Eleftheratos et al, 2014).…”
Section: Fountoulakis Et Al: Short-and Long-term Variability Of Smentioning
confidence: 99%
“…Signs from the onset of ozone recovery since the late 1990s on surface UV-B irradiance have been mainly detected over the northern high latitudes; recent studies indicate that UV-B has been declining during the last 2 decades (Bernhard, 2011;Eleftheratos et al, 2014). However, during the same period, both the UV-B and the UV-A irradiance are increasing over many locations in the Northern Hemisphere mid-latitudes, mainly due to the negative trends in the amount of clouds and aerosols (De Bock et al, 2014;Fitzka et al, 2012;Román et al, 2015;Smedley et al, 2012;Zerefos et al, 2012). In a recent study, Fragkos et al (2015) showed that in Thessaloniki, even under extreme high (low) total ozone column (TOC) conditions, the erythemal irradiance can be lower (higher) than its climatological values due to the dominant effect of aerosols.…”
Section: Fountoulakis Et Al: Short-and Long-term Variability Of Smentioning
confidence: 99%
“…This period of decrease is followed by a period of significant increase (Steinbrecht et al, 2006;Harris et al, 2008;Vigouroux et al, 2008;Krzýscin and Borkowski, 2008;Herman, 2010;Bais et al, 2011). For the period before the mid-1990s, studies report on decreasing ozone values at Brussels (Bojkov et al, 1995 andZerefos et al, 1997), Reading (Bartlett and Webb, 2000), Lerwick (Smedley et al, 2012), Arosa (Bojkov et al, 1995 andStaehelin et al, 1998), Hohenpeissenberg (Bojkov et al, 1995), Sodankylä (Glandorf et al, 2005) and Thessaloniki (Glandorf et al, 2005) (see Table 7). After the mid-1990s, most studies report on a plateau or a limited increase in ozone.…”
Section: Total Ozone Columnmentioning
confidence: 99%
“…The ozone depletion not only occurred above the Antarctic; there is strong evidence that stratospheric ozone also diminished above midlatitudes (Bartlett and Webb, 2000;Kaurola et al, 2000;Smedley et al, 2012). While ozone depletion continued in the 2000s over the polar regions, it has leveled off at midlatitudes, although ozone amounts still remain lower compared to the amounts in the 1970s (Garane et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric ozone can be discounted due to a similar rate of decrease being observed at measuring sites at Lerwick and Southern England since 1979 (5.8% and 4.8% respectively) (Smedley et al 2012). It is therefore assumed that the effect of stratospheric ozone on annual UVR variation between regions of the UK is very low.…”
Section: Discussionmentioning
confidence: 96%